Optimized enzyme-aided extraction enhances recovery of carotenoids from tomato peel and improves the biological activity - NAYELY LEYVA-LÓPEZA; BENIGNO VALDEZ-TORRESA; FRANCISCO DELGADO-VARGASB; RAYMUNDO S. GARCÍA-ESTRADA; J. BASILIO HEREDIAA (International Journal of Pharma and Bio Sciences, 2017)
There is an increasing interest in carotenoids in pharmaceutical and nutraceutical industry due to their antioxidant and antimutagenic potential. Tomato peel residue from the processing industry represents an environmental problem. However, the peel still has a high content of carotenoids that can be used as functional ingredients in the development of new products. Due to carotenoids are inside the plant cell its recovery with solvents became difficult, so the use of enzymes is proposed to overcome this situation. The aim of this study was to optimize the enzyme-aided carotenoid extraction from tomato peel without affecting its biological functionality. The optimum conditions of enzyme percentage and incubation time were obtained by using response surface methodology. For the carotenoid extraction a mixture of hexane:acetone:ethanol (50:25:25, v/v/v) was used. The identification of particular carotenoids, antioxidant and antimutagenic activity were determined by HPLC, TEAC and Ames Test, respectively. The carotenoid recovery at optimum macerating conditions (10.24%, 4.8 h) increased 22% as compared with the untreated sample. From the total of carotenoids, lycopene obtained by enzymatic maceration represented 82% and β-carotene 10.5%, the rest were unidentified compounds. Moreover, the carotenoids obtained by enzymatic treatment presented higher antioxidant and antimutagenic activity than those obtained from the untreated peel.